An Analysis of Political Ambition in Britain. Issue 1 (17th January 2018) - Allen, Peter; Cutts, David
Abstract: Representative democracies require sufficient numbers of citizens to put themselves forward as candidates for political office. Existing studies have shown that political institutions are not representative of the population as a whole, suggesting that political ambition is not evenly distributed across all potential candidates. We discuss evidence from the first systematic study of political ambition in Britain, examining the question of who is interested in putting themselves forward for political office. We find patterns in the distribution of political ambition that help to explain why British political institutions do not look like the British people as a whole and include a gender gap, a social class gap, an education gap, a north–south divide, and a personality gap. We discuss the implications of our findings for political parties, arguing that they need to adjust practices of candidate recruitment in such a way that minimises the effects of these biases.